Analisis Fatwa di Indonesia tentang Kemahraman Akibat Donor ASI: Kajian terhadap Fatwa MUI, NU, dan Muhammadiyah - Saifulloh; Hidayati, Tri Wahyu (Pascasarjana IAIN Sultan Amai Gorontalo, 2023)
Through Government Regulation No. 33 of 2012 Article 11 on Exclusive Breastfeeding, it is known that breast milk donation is a legal act according to the law. Among its provisions is that it must be implemented in accordance with religious norms, including through fatwas. The fatwa of the Indonesian Ulema Council (MUI) is widely used as a reference by the Indonesian people because of its status as a government organization, the fatwa of Nahdlatul Ulama (NU), and the fatwa of Muhammadiyah is also the same because the the two largest religious institutions in Indonesia. This article aims to discover the reality of breast milk donation in Indonesia and analyze the fatwas of the Indonesian Ulema Council (MUI), Nahdlatul Ulama (NU), and Muhammadiyah on the permissibility of breast milk donation. The author uses a literature study method presented descriptively analytically of the fatwa content and istinbath used. The result of this article is that the views and fatwas issued by the Indonesian Ulema Council (MUI), Nahdlatul Ulama (NU), and Muhammadiyah regarding the mahram status arising from breast milk donation, have some differences in legal istinbath and interpretations that exist in their views.